PENGARUH DOPING CuO TERHADAP EFFESIENSI SEL SURYA POLIMER HIBRID BERSTRUKTUR TERBALIK - Putri, Shintya (RC-INSTITUT, 2019)
One of the most usable polymers is PPV:PCBM, PPV polymer mixed with PCBM polymer with ratio 3:1 can generate higher efficiency rate compared to the others. When preparing the solar cell, the available hybrid polymer has ITO/PEDOT:PSS/PPV:PCBM/Carbon lithography structure, however the solar cell of this kind has some problems which is PEDOT:PSS tend to became hygroscopic when placed in the bottom layer will absorb more water until the performance of the solar cell decreases. This study will discuss hybrid polymer solar cell with reversed structure, where the PEDOT:PSS layer will be placed on the uppermost to avoid the lack of previously built solar cells, and CuO also used in this solar cells as doping to increase the efficiency rate of the solar cells. As a doping, the concentration of CuO will be varied from 0.5 mole and 0.75 mole. In the other side, the thick coating of CuO also varied from 1x, 2x and 3x. All prepared solar cells then characterized using X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) to determine the crystal size, the thick of the layer and the surface’s morphological structure, 4-point probe system to measure the efficiency rate. The result of the CuO doping proved to be able to increase the efficiency rate of the previously built solar cells with the highest efficiency rate result is 3.237% with the 1 mole concentration of CuO and 1x coating. The crystal size of CuO was 23.19 – 23.25 nm.